The ocular cardiac reflex effect study on cardiac hemodynamic parameters in healthy young mans - Palamarchuk, A. I. (Modern medical technology, 2019)
Purpose of the study. Investigate changes of cardiac hemodynamic parameters caused by ocular cardiac reflex triggering in healthy men’s in youthful age. Material and methods. 120 healthy male volunteers in youthful age were examined. The mean age was (19,2 ± 0,93 years). For ocularcardiac reflex (OCR) triggering we used a patented model «Device for dosed compression effects on the eyeballs» and «The method of ocular cardiac reflex triggering». On the basis of the obtained parameters of systolic (SBP) and diastolic (DBP) blood pressure, by arithmetic operations, pulse pressure (PP) and average flow pressure (AFP) and integrative parameters of cardiohemodynamics (CHD) – systolic blood volume (SBV), minute blood flow volume (MBFV), volumetric blood flow rate (V), total peripheral resistance (TPR) were determined. Results. Three main types of cardiovascular system response on OCR triggering were identified. The first type – hypertensive (n = 30 (25%) of the total number of examined subjects) was characterized by a significant (p < 0,05) increase in heart rate, SBP, DBP, PP, AFP and other integrative parameters of CHD. The second, hypotonic type of the response (62 subjects; 51,7%) was characterized by a significant (p < 0,05) decrease in SBP, DBP, PP, AFP. Patients with third, dystonic type, of response (n = 28 (23,3%) of the total number examined subjects) showed significant bilateral changes of blood pressure parameters in a nonlinear dependence of compression power on the eyeballs. Determination CHD parameters directly after and 3 and 5 minutes after decompression of the air in the compression device we enabled to determine the subtype of the mobility of the nervous centers as a feature that complements the basic type. The subtype of normal mobility was revealed in 63,3% (n = 19) of subjects with the main hypertensive type of response, 69,3% (n = 43) of subjects with the main hypotonic and 60,7 % (n = 17) with the main dystonic type of response of the cardiovascular system. The inert subtype in the mobility of the cardiovascular system were identified in 36,7% (n = 11) individuals with hypertension is the main type of response, at 30,7% (n = 19) of individuals with primary hypotonic type of response and 39,3 % (n = 11) – distancing. The obtained typological changes in blood pressure parameters caused by OCR triggering allowed to reveal predisposition to hypertension, hypotension, dystonia and to predict the development of hypertension in patients with hypertensive type of response usin appropriate primary prevention changes in life style. The highest risk of hypertension development may be in persons with hypertensive inert type of reaction of the system of regulation of blood pressure on OCR triggering. Further studies are being conducted to confirm this assumption.